Comparison of the genetic variation of captive ring‐tailed lemurs with a wild population in Madagascar. Issue 5 (29th May 2015) - Pastorini, Jennifer; Sauther, Michelle L.; Sussman, Robert W.; Gould, Lisa; Cuozzo, Frank P.; Fernando, Prithiviraj; Nievergelt, Caroline M.; Mundy, Nicholas I.
<x xml:space="preserve">Abstract</x> Genetic variability among captive and wild ring‐tailed lemurs (Lemur catta) was assessed using mitochondrial and nuclear DNA data. A 529 bp segment of mtDNA was sequenced and 9 microsatellite loci were genotyped for 286 ring‐tailed lemurs. Samples were obtained from the well‐studied L. catta population at the Bezà Mahafaly Special Reserve and from captive animals at six institutions worldwide. We found evidence of possible patrilineal contribution but the absence of matrilineal contribution from the Bezà area, and haplotypes not found in Bezà but present in Ambohimahavelona, Andringitra Massif, and other unknown locations, in the sampled captive population, indicating that the founders of the captive population originated from a wide geographic range. Total genetic variation and relatedness in captive L. catta in the six institutions were similar in extent to that of the wild population in Bezà. Based on the diverse origins of the captive population founders our results suggest the erosion of genetic diversity in the captive population. Sampled individuals from the same institution were more closely related to each other than members of a social group in the wild. Individuals housed at different institutions were less closely related than those of different social groups at Bezà, indicating lower genetic exchange between captive institutions than between social groups in a locality in the wild. Our findings underscore the usefulness of genotyping in determining the geographic origin of captive population founders, obtaining pedigree information if paternity is uncertain, and in maximizing preservation of extant genetic diversity in captivity. Zoo Biol. 34:463–472, 2015. © 2015 Wiley Periodicals, Inc.